STATIC AND PESUDOSTATIC SLOPE ANALYSIS USING MORGENSTER-PRICE METHOD (Study case Embung Unpad, Jatinangor, West Java, Indonesia) - Khoirullah, Nur; Mahayana, Ringkang Gumiwang; Sugiawati, Gisa Nurputri; Sophian, R. Irvan (Fakultas Teknik Geologi Universitas Padjadjaran, 2025)
Infrastructure areas require preliminary geotechnical analysis, which includes slope design and periodical evaluation for assessing changes in geotechnical conditions due to the influence of earthquake loads, human activities, and environmental changes. Factors such as rainfall, groundwater level and earthquake vibrations play an important role in influencing slope stability, so slope stability analysis is an aspect that needs to be considered in geotechnical engineering, especially in areas prone to seismic activity. This research aims to evaluate slope stability using the Morgenstern-Price method, which combines static and pseudo-static conditions to assess the impact of seismic loads. This research focuses on analyzing slope stability in the Embung Unpad area, Jatinangor, which is located in a seismically active zone. The slope is characterized by volcanic soil derived from weathered young volcanic rocks, with slopes varying from moderate to steep. This research focuses on comparing 2D and 3D analysis approaches to determine their accuracy and reliability in capturing critical slope stability factors in seismic scenarios. In the analysis, the stability of the slope is calculated using the statistical-probabilistic method to determine the percentage of slope failure. The simulation results show that the stability analysis using the 3D approach produces a higher safety value than the 2D approach, namely FoS value of 0.955 in 3D analysis and FoS value of 0.913 in 2D analysis. 3D analysis is generally able to capture the complexity of slope geometry and parameters more thoroughly than 2D approach, one of which can evaluate the landslide mechanism in 3D characterized by the landslide volume that can occur. However, since the 3D model in this study is the result of 2D extrude model and consists of 1 material, the model in this study has lower complexity than if the constituent materials are heterogeneous. However, this study has the limitation that the 3D model is the result of extruded volume from 2D geometry with the result that the difference in FoS value is relatively similar between 3D and 2D models. This research highlights the importance of detailed analysis of slope safety risks in seismically active areas to ensure the sustainability and safety of surrounding infrastructure.